Convexity properties for certain classes of analytic functions associated with an integral operator - Wongsaijai,B. (Hindawi Publishing Corporation, 2015)
© 2014 Ben Wongsaijai and Nattakorn Sukantamala. We introduce a new form of generalized integral operator defined on the class of analytic functions A 0. By making use of this novel integral operator, we give the convexity of other integral operators. We also briefly indicate the relevant connections of our presented results to the formerly reported results. Furthermore, other interesting properties are also discussed.